2021
DOI: 10.1088/2057-1976/ac19cf
|View full text |Cite
|
Sign up to set email alerts
|

Advanced imaging of dentin microstructure

Abstract: This study aimed to demonstrate the feasibility of using optical coherence tomography (OCT) for locating the sectioning site of a specimen before characterizing the ultrastructural features of dentin surfaces as well as the inner wall of the dentinal tubules (DT) using a field emission scanning electron microscope (FESEM). Eight sound human molar teeth were extracted, examined via crosspolarization optical coherence tomography (CP-OCT), embedded, and hemisectioned using a lowspeed diamond sawing machine. Next,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…It was concluded that another method of fixation and sample preparation was required that would allow both thicker samples and the hydroxyapatite to remain within the CEA sections. Previously, teeth have been sectioned by embedding the tooth in epoxy resin and sectioning using a low-speed cutting machine under a water coolant . Hydroxyapatite is the main mineral in the enamel of teeth, and as it is also found in atherosclerotic plaques, this suggests this method would be suitable for sectioning of the plaques.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was concluded that another method of fixation and sample preparation was required that would allow both thicker samples and the hydroxyapatite to remain within the CEA sections. Previously, teeth have been sectioned by embedding the tooth in epoxy resin and sectioning using a low-speed cutting machine under a water coolant . Hydroxyapatite is the main mineral in the enamel of teeth, and as it is also found in atherosclerotic plaques, this suggests this method would be suitable for sectioning of the plaques.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, teeth have been sectioned by embedding the tooth in epoxy resin and sectioning using a low-speed cutting machine under a water coolant. 31 Hydroxyapatite is the main mineral in the enamel of teeth, 32 and as it is also found in atherosclerotic plaques, this suggests this method would be suitable for sectioning of the plaques. Samples were fixed in glutaraldehyde and embedded in epoxy resin.…”
Section: Resultsmentioning
confidence: 99%
“…It was also suggested that an increase in temperature may lead to a release of the resin monomer [ 41 ]. Another study concluded that CS did not affect the surface roughness of composite restorations; however, it influenced the surface gloss and increased the staining possibilities due to the interaction between CS and composite filler content [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tars contain pigmented compounds and metal ions, such as lead and cadmium [ 8 ]. Dentin is a heterogeneous, wet, and organic substrate compared to enamel, making bonding to this substrate more challenging [ 10 , 11 ]. Proper adhesion mandates intimate contact with the tooth surface when bonding restorative materials to dental substrates.…”
Section: Introductionmentioning
confidence: 99%
“…This technique has many merits, including non-invasiveness, visibility of hard and soft tissues, and lack of radiation with excellent spatial resolution [ 26 , 27 ]. OCT allows for real-time imaging of tissue sections without the need for biopsy, histological procedures, or X-rays, in a non-contact and non-invasive manner [ 28 , 29 , 30 , 31 ]. The benefits mentioned have been verified in a prior investigation that established the capability of MCT and OCT to identify, without causing damage, the sealing ability of the pulp-capping agents in primary teeth.…”
Section: Introductionmentioning
confidence: 99%